2001
DOI: 10.1002/cbf.910
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sarcolemma and sarcoplasmic reticulum isolated from skeletal muscle of the freeze tolerant wood frog, Rana sylvatica: the β2‐adrenergic receptor and calcium transport systems in control, frozen and thawed states

Abstract: In freeze tolerant wood frog Rana sylvatica, the freeze-induced liberation of glucose plays a critical role in survival in response to sub-zero temperature exposure. We have shown that the glycaemic response is linked to selective changes in the expression of hepatic adrenergic receptors through which catecholamines act to produce their hepatic glycogenolytic effects. The purpose of the present study was to determine if skeletal muscle, another catecholamine-sensitive tissue with glycogenolytic potential, disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…By contrast, past studies would suggest a need for PKC to remain active in muscle; these have shown that in response to freezing, IP 3 levels rose moderately, by 55%, in skeletal muscle (Holden & Storey, 1996; Holden & Storey, 1997). Moreover, calcium binding and uptake into the sarcoplasmic reticulum were strongly decreased in skeletal muscle of frozen frogs, leading to increased cytosolic calcium levels (Hemmings & Storey, 2001). However, in yet other studies, muscle IP 3 levels remained constant in frogs subjected to short-term anoxia at 5 °C, and then fell by 40% after 2 days of anoxic exposure.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, past studies would suggest a need for PKC to remain active in muscle; these have shown that in response to freezing, IP 3 levels rose moderately, by 55%, in skeletal muscle (Holden & Storey, 1996; Holden & Storey, 1997). Moreover, calcium binding and uptake into the sarcoplasmic reticulum were strongly decreased in skeletal muscle of frozen frogs, leading to increased cytosolic calcium levels (Hemmings & Storey, 2001). However, in yet other studies, muscle IP 3 levels remained constant in frogs subjected to short-term anoxia at 5 °C, and then fell by 40% after 2 days of anoxic exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that glycogenoloysis is stimulated by peripheral freezing through hormone-based mechanisms, such as -adrenergic signalling (Hemmings and Storey, 1994;Hemmings and Storey, 2001;Storey and Storey, 2004). It is possible that GSK-3 activation is mediated by similar hormonal action.…”
Section: Discussionmentioning
confidence: 99%
“…SERCA regulation in anoxic turtles of overall ATP hydrolyzed (Hochachka et al, 1996). Indeed, it has been shown that Na + /K + -ATPase and SERCA are closely regulated and are strongly suppressed in hypometabolic states including hibernation, estivation and diapause (MacDonald and Storey, 1999;Hemmings and Storey, 2001;Malysheva et al, 2001;Ramnanan and Storey, 2006;Ramnanan and Storey, 2008;McMullen and Storey, 2008). Anoxia has been shown to suppress SERCA activity in neurons (Henrich and Buckler, 2008) and hypoxia decreased SERCA expression in hearts (Pei et al, 2003) of rats.…”
Section: Discussionmentioning
confidence: 99%